Late Iron Age gold hoards from the Low Countries and the Caesarian conquest of Northern Gaul
1 online resource (248 pages)
Keywords: This volume presents eight new Iron Age gold hoards from the southern Netherlands and Belgium, consisting of gold coinages and in several cases also gold ornaments. The study of these hoards provides a wealth of new information on the archaeological contexts in which they were found, on the dating of many coin types and jewellery, and on the social role of gold in pre-Roman society. All these hoards seem to have been buried in the 50s BC, thus making a direct association with the historical context of Caesar's war campaigns in Northern Gaul very plausible. This makes the volume important for archaeologists as well as numismatists and historians.Amsterdam Archaeological Studies is a series devoted to the study of past human societies from the prehistory up into modern times, primarily based on the study of archaeological remains. The series will include excavation reports of modern fieldwork; studies of categories of material culture; and synthesising studies with broader images of past societies, thereby contributing to the theoretical and methodological debates in archaeology.